Martius graft transposition: a successful procedure for the ultimate repair of the anovaginal/rectovaginal fistula - Mohamed A Boghdady; Hossam H Soliman (Journal of Medicine in Scientific Research, 2020)
Background Recto/ano-vaginal fistula (RAVF) is one of the worst medical conditions that could lead a lady to suffer in her life. It represents a horrendous experience that might put the lady suffering that ailment not only on the brink of abandoning her social life, but even disrupting her marital life and breaking the integrity of her family. There are various operative methods implemented all over the past decades aiming to cure such medical condition. Of those, interposing a vascularized tissue flap is suggested as an operative solution to guarantee long term successful healing. Of which the most commonly tried is the bulbocavernous flap technique. Patients and methods Eighteen patients with both low and mid recto/ano-vaginal fistula,were repaired using martius graft transposition technique. And all fistulas were at least 8 months old. All patients were followed up for around one year postoperative for assessment of fistula healing and any associated persistent complications and side effects. Results All of the 18 patients included in the current study, were fully cured with no recurrence of fistula on one year follow up term, with 13 patients complaining mild dyspareunia that didn't hamper them resuming their sexual life. Out of eight patients with low fistula, of whom four had an old complete perineal tear with severed sphincter. five patients almost regained full control over flatus and stools. While two patients reported appreciably partial control over flatus and liquid stools. Conclusion Dissection and mobilization of fibrofatty graft (Martius graft) from the labia majora with intact blood supply for enforcing and supporting the site of repaired fistula is better than gracilis and gluteus grafts in surgical repair of recto/ano-vaginal fistula.